1998
DOI: 10.1128/jcm.36.5.1193-1196.1998
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Follow-Up by Serology of Patients Given Antibiotic Treatment for Helicobacter pylori Infection

Abstract: Helicobacter pylori serology and in particular enzyme-linked immunosorbent assays for the measurement of immunoglobulin G (IgG) antibody titers form an accurate means of diagnosing H. pylori infection in patients before treatment. H. pylori serology is of limited value in monitoring treatment because of the slow decline in antibody titers. In the present study we aimed to measure the most suitable moment after antibiotic treatment at which serology should be used to monitor treatment. Sixty-four patients who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…For evaluative purposes, the sensitivity and specificity are less useful (83). On the basis of the receiver operating characteristic (ROC) curve, we calculated the AURC, which is a measure for the diagnostic performance of a test (42). It is independent of cutoff points and reasonably immune to selection bias.…”
Section: Data Collection and Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…For evaluative purposes, the sensitivity and specificity are less useful (83). On the basis of the receiver operating characteristic (ROC) curve, we calculated the AURC, which is a measure for the diagnostic performance of a test (42). It is independent of cutoff points and reasonably immune to selection bias.…”
Section: Data Collection and Extractionmentioning
confidence: 99%
“…However, ROC curves and/or test result distributions were very sparsely presented in the publications. Fortunately, it is possible to make a fairly accurate estimation of the underlying ROC curve if one sensitivity and one specificity are mentioned (42). We think that this method is more appropriate for evaluation of the diagnostic performance of tests than the summary ROC (48).…”
Section: Implementation Of Diagnostic Testsmentioning
confidence: 99%
“…Serological tests are noninvasive and are used to detect immunoglobulin (Ig) G, IgA and IgM antibodies in the sera of H pyloriinfected subjects. The ELISA test is the most widely used test for the detection of such antibodies in epidemiological studies (4,21,22). Immunoblot assay enables the detection of antibodies against specified H pylori antigens, such as CagA and VacA antigens (21,23).…”
mentioning
confidence: 99%
“… 7 A recent study showed that IgG titres for H. pylori fall sufficiently 10 weeks after therapy for treatment success to be established. 8 In this present study, less than half the patients had a sufficient decline in IgG antibody titres 8 weeks after treatment for cure of infection to be established. The latex test showed even less predictive power with only one‐third of patients giving a negative result at this time point.…”
Section: Discussionmentioning
confidence: 51%